2012
DOI: 10.5539/ijel.v2n4p101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using Mnemonic Associations on Vocabulary Recall of Iranian EFL Learners over Time

Abstract: Effects of using mnemonic associations on vocabulary recall of Iranian EFL learners were investigated in two separate experiments with adolescents and adults. In each experiment, the students were divided into two groups of experimental (mnemonic) and control (rote). Using a number of predesigned (the researcher-designed) associations as models, the students of the mnemonic groups were trained to generate mnemonic associations of their own for the new vocabulary words they had chosen to learn. Then, their use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…One prominent mnemonic strategy, the keyword method, stands out for its efficacy in enhancing vocabulary acquisition, particularly in children and learning-disabled students (Mastropieri et al, 1985) findings reinforce the superiority of the keyword method over the context method in both immediate and delayed recall and recognition of vocabulary. Anjomafrouz and Tajalli's (2012) study further highlights the benefits of mnemonic devices, specifically among adult and teenage EFL students. The comparison of mnemonic associations with repetition underscores the superior performance of the mnemonic group.…”
Section: Literature Review 21 Comparative Analysis Of Mnemonic and No...mentioning
confidence: 67%
“…One prominent mnemonic strategy, the keyword method, stands out for its efficacy in enhancing vocabulary acquisition, particularly in children and learning-disabled students (Mastropieri et al, 1985) findings reinforce the superiority of the keyword method over the context method in both immediate and delayed recall and recognition of vocabulary. Anjomafrouz and Tajalli's (2012) study further highlights the benefits of mnemonic devices, specifically among adult and teenage EFL students. The comparison of mnemonic associations with repetition underscores the superior performance of the mnemonic group.…”
Section: Literature Review 21 Comparative Analysis Of Mnemonic and No...mentioning
confidence: 67%
“…Cohen and Aphek (1980) stated that those using the association method learn memorizing words faster and are more successful in learning when compared to those not using that method. Anjomafrouz and Tajalli (2012), examining the rate of success of Iranian students in learning words by an association method, found that using mnemonic associations led to significantly better performance of adult students when a comparison was made with respect to an external control group (rote group) and better performance of both adult and adolescent groups when a comparison was made with respect to an internal control group (when students used no associations in the mnemonic group).…”
Section: Discussionmentioning
confidence: 99%
“…The acronym method, (abbreviation or combination of letters) is a method used by PAUD Mikhrajul Ulum to make it easier for PAUD students to remember or memorize words and letters. This acronym method (Figure 3) is the same as the singing method (Amiryousefi & Ketabi, 2011;Anjomafrouz & Tajalli, 2012). However, this acronym method only uses word abbreviations or letter abbreviations such as the letters Idghom which are combined into the word yarmaluna (ya', ro', mim, lam, waw, nun).…”
Section: Figure 2 Example Of Tajweed Materials Singing Methodsmentioning
confidence: 99%